Faktor-Faktor Penentu yang Mempengaruhi Tata Kelola: Tinjauan Literatur Sistematis dan Sintesis untuk Penelitian di Masa Depan - Muslikun Mashadi; Theresia Trisanti; Wisnu Prajogo (JURNAL ILMIAH GEMA PERENCANA, 2025)
Effective governance is crucial for accountability, transparency, and efficiency within the public sector. Originating from corporate governance principles like accountability and transparency, it expanded to the public sector, exemplified by frameworks such as the UNDP's good governance initiative. Its implementation faces diverse challenges globally, including corruption in emerging nations and bureaucratic efficiency in affluent ones, highlighting the need for a comprehensive analysis of its determinants. This study aims to uncover the determinants influencing governance and their effects on public accountability, operational efficiency, and social welfare. This research employs a Systematic Literature Review (SLR) methodology following PRISMA principles. A Scopus database search using keywords "Governance" and "Ministry OR Central Government OR Department OR Federal" initially yielded 281 articles, subsequently refined to 83 relevant articles. Bibliometric analysis using VOS viewer identified "Governance" as a central theme, closely linked to "government" and "ministry," and indicated a rising research interest from 2010 to 2024. The synthesis of findings reveals that key determinants of governance include stakeholder engagement, robust leadership, policy quality, public participation, and fiscal resources. These factors significantly enhance accountability and transparency, improve policy quality and service efficiency, mitigate corruption, and contribute to economic efficiency and an improved quality of life. Future governance research should focus on multilateral coordination, technology application (e-government, big data), adaptive leadership, decentralization, and sustainable natural resource management to address global challenges.